Interplay of temperature, thermal‐stresses and strains in laser‐assisted modification of collagenous tissues: Speckle‐contrast and OCT‐based studies. Issue 1 (9th October 2019) - Baum, Olga I.; Zaitsev, Vladimir Y.; Yuzhakov, Alexey V.; Sviridov, Alexander P.; Novikova, Maria L.; Matveyev, Alexander L.; Matveev, Lev A.; Sovetsky, Alexander A.; Sobol, Emil N.
Abstract: Moderate heating of collagenous tissues such as cartilage and cornea by infrared laser irradiation can produce biologically nondestructive structural rearrangements and relaxation of internal stresses resulting in the tissue reshaping. The reshaping results and eventual changes in optical and biological properties of the tissue strongly depend on the laser‐irradiation regime. Here, a speckle‐contrast technique based on monochromatic illumination of the tissue in combination with strain mapping by means of optical coherence elastography (OCE) is applied to reveal the interplay between the temperature and thermal stress fields producing tissue modifications. The speckle‐based technique ensured en face visualization of cross correlation and contrast of speckle images, with evolving proportions between contributions of temperature increase and thermal‐stresses determined by temperature gradients. The speckle‐technique findings are corroborated by quantitative OCE‐based depth‐resolved imaging of irradiation‐induced strain‐evolution. The revealed relationships can be used for real‐time control of the reshaping procedures (e.g., for laser shaping of cartilaginous implants in otolaryngology and maxillofacial surgery) and optimization of the laser‐irradiation regimes to ensure the desired reshaping using lower and biologically safer temperatures. The figure of waterfall OCE‐image demonstrates how the strain‐rate maximum arising in the heating‐beam center gradually splits and drifts towards the zones of maximal thermal stresses located at the temperature‐profile slopes. Abstract : Moderate short‐time heating of cartilage and cornea by infrared‐laser irradiation can produce biologically nondestructive tissue reshaping, which can be used for fabrication of cartilaginous implants and cornea‐refraction correction. We show that thermal stresses can help to produce efficient reshaping at lower temperature outside the temperature maximum. OCT‐based visualization demonstrates how the strain‐rate maximum arising in the heating‐beam center gradually splits and drifts towards the temperature‐profile slopes, where maximal thermal stresses are located.